2014
DOI: 10.1093/mnras/stu1099
|View full text |Cite
|
Sign up to set email alerts
|

The halo+cluster system of the Galactic globular cluster NGC 1851★

Abstract: NGC 1851 is surrounded by a stellar component that extends more than ten times beyond the tidal radius. Although the nature of this stellar structure is not known, it has been suggested to be a sparse halo of stars or associated with a stellar stream. We analyse the nature of this intriguing stellar component surrounding NGC 1851 by investigating its radial velocities and chemical composition, in particular in comparison with those of the central cluster analysed in a homogeneous manner. In total we observed 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 94 publications
(147 reference statements)
4
80
1
Order By: Relevance
“…Figures 1 and 3 show that a majority of stars having velocities consistent with cluster membership reside inside 4′ of the cluster center, but the obvious field stars are more uniformly distributed. Additionally, Johnson et al (2015b) and Yong et al (2016) have shown that most NGC 6273 stars have [Fe/H]  −1.35, but such stars are relatively rare in the bulge field (e.g., Zoccali et al 2008;Bensby et al 2013;Johnson et al 2013;Ness et al 2013b (Grillmair et al 1995;Olszewski et al 2009;Marino et al 2014b;Navin et al 2015Navin et al , 2016Kuzma et al 2016). Figure 1 shows a possibly interesting morphology such that stars near the edge of our observations, which are also close to the tidal radius, are more numerous on the eastern side of the cluster than the western side.…”
Section: Radial Velocities and Cluster Membershipmentioning
confidence: 71%
“…Figures 1 and 3 show that a majority of stars having velocities consistent with cluster membership reside inside 4′ of the cluster center, but the obvious field stars are more uniformly distributed. Additionally, Johnson et al (2015b) and Yong et al (2016) have shown that most NGC 6273 stars have [Fe/H]  −1.35, but such stars are relatively rare in the bulge field (e.g., Zoccali et al 2008;Bensby et al 2013;Johnson et al 2013;Ness et al 2013b (Grillmair et al 1995;Olszewski et al 2009;Marino et al 2014b;Navin et al 2015Navin et al , 2016Kuzma et al 2016). Figure 1 shows a possibly interesting morphology such that stars near the edge of our observations, which are also close to the tidal radius, are more numerous on the eastern side of the cluster than the western side.…”
Section: Radial Velocities and Cluster Membershipmentioning
confidence: 71%
“…Lastly, Olszewski et al (2009) uncovered the existence of a stellar halo surrounding the cluster, that is at least 500pc in diameter. NGC 1851 halo stars have been identified through radial velocities (e.g., Marino et al 2014;Navin, Martell & Zucker 2015) and have been found to exhibit the same s-process abundance patterns as the bright sub-giant branch stars within the cluster, confirming that the envelope is directly related to NGC 1851 (Marino et al 2014).…”
Section: Introductionmentioning
confidence: 71%
“…Indeed, deviations from the sharply truncated King phase space distribution (e.g., see the cases of NGC 1851, as studied by Olszewski et al 2009;Marino et al 2014, NGC 5694 by Correnti et al 2011;Bellazzini et al 2015, and several others, as discussed, e.g., by Carballo-Bello et al 2018), spherical symmetry (e.g., Chen & Chen 2010), and pressure isotropy (e.g., van de Ven et al 2006;Bellini et al 2014Bellini et al , 2017Watkins et al 2015) are found in a growing number of GGCs. Also the observational evidence of systemic rotation is increasing (e.g., Anderson & King 2003;Lane et al 2009Lane et al , 2010Bellazzini et al 2012;Bianchini et al 2013;Fabricius et al 2014;Kacharov et al 2014;Kimmig et al 2015;Lardo et al 2015;Bellini et al 2017;Boberg et al 2017;Cordero et al 2017;Ferraro et al 2018b;Kamann et al 2018), possibly suggesting that, when properly surveyed, the majority of GCs rotate at some level.…”
Section: Introductionmentioning
confidence: 93%